Effective communication between users and the multidisciplinary team of the human milk bank in the eastern Amazon (Research, Society and Development, 2022)
The HMB's main function is to provide assistance to children's health in the country. than 1.1 million Brazilian women. Objective: to identify the effective communication of the multidisciplinary team in the Human Milk Bank (HMB) to promote breastfeeding. Methodology: The methodological strategy of action research used for development, through an exploratory study, supported by the term transversal orality, with a quanti-quali approach. Participated in the study 19 professionals who make up the multidisciplinary team of the Human Milk Bank (BLH) - Dr. João Aprígio – from the Santa Casa de Misericórdia do Pará Foundation – FSCMP. Results: the construction of a strategy that favors effective communication between users and professionals of the Human Milk Bank (BLH)- Dr. João Aprígio – from Fundação Santa Casa de Misericórdia do Pará - FSCMP, a tool capable of promoting breastfeeding and mobilizing society to support women's demands. Conclusion: It is suggested, in order to have a future perspective, to present a technical opinion for middle management as a suggestion of strategies for the execution and implementation of a tool capable of favoring effective communication between users and the multidisciplinary team of a highly complex service. In addition, present a proposal for the creation and validation of an accessible and practical mobile application based on a real diagnosis.